Connection Between Leadership and Communication - Dajnoki, Krisztina (Acta Agraria Debreceniensis, 2003)
Discussing communicationis not an easy job as it is about one of the most important symptomps of life, which plays an important role in all social humanic processes. Ways and devices of communication, communicational system of society developed – while in constant connection – with daily activity, social relations, bodies and structure of society.Communication takes a prominent part in all forms of management. By the help of this article I would like to demonstrate what importance communication has according to literarure and what relationship can be experienced between communication and management. Is D’Aprix statement reliable saying “communication is management or more properly drafted management is communication”?!